Europe's Islamic tightrope - Acharya, Arabinda (2021)
Targeted police actions against certain groups in Austria and proposed legislation to regulate Islamic religious and cultural practices in France suggest that some parts of Europe seem to be resetting their relations with Muslim societies. For better or for worse, Europe’s relations with Muslim communities may be evolving.